Neural probe system for behavioral neuropharmacology by bi-directional wireless drug delivery and electrophysiology in socially interacting mice - Yoon, Yousang; Shin, Hyogeun; Byun, Donghak; Woo, Jiwan; Cho, Yakdol; Choi, Nakwon; Cho, Il-Joo (Nature Publishing Group, 2022)
Technologies for monitoring electrophysiological effects of drugs in behaving animals have limitations. Here the authors report a wireless neural probe system with drug delivery capability for real-time monitoring of drug effects. Assessing the neurological and behavioral effects of drugs is important in developing pharmacological treatments, as well as understanding the mechanisms associated with neurological disorders. Herein, we present a miniaturized, wireless neural probe system with the capability of delivering drugs for the real-time investigation of the effects of the drugs on both behavioral and neural activities in socially interacting mice. We demonstrate wireless drug delivery and simultaneous monitoring of the resulting neural, behavioral changes, as well as the dose-dependent and repeatable responses to drugs. Furthermore, in pairs of mice, we use a food competition assay in which social interaction was modulated by the delivery of the drug, and the resulting changes in their neural activities are analyzed. During modulated food competition by drug injection, we observe changes in neural activity in mPFC region of a participating mouse over time. Our system may provide new opportunities for the development of studying the effects of drugs on behaviour and neural activity.